2011
DOI: 10.1175/2010jcli3713.1
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Heat Transport as a Cause for Model Uncertainty in Projected Arctic Warming

Abstract: The Arctic climate is governed by complex interactions and feedback mechanisms between the atmosphere, ocean, and solar radiation. One of its characteristic features, the Arctic sea ice, is very vulnerable to anthropogenically caused warming. Production and melting of sea ice is influenced by several physical processes. The authors show that the northward ocean heat transport is an important factor in the simulation of the sea ice extent in the current general circulation models. Those models that transport mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
74
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 41 publications
10
74
3
Order By: Relevance
“…An assessment of all terms of the Arctic heat budget and the feedback mechanisms leading to Arctic Amplification is, however, beyond the scope of our paper. The magnitude of TO-HTR changes appears to play a decisive role in the amplitude of pan-Arctic warming, and sea-ice evolution in climatechange simulations (Mahlstein and Knutti, 2011). These authors concluded that the TOHTR changes contribute significantly to Arctic amplification, but they also identified considerable differences in the TOHTR magnitude in the CMIP3 model suite as a cause for model uncertainty in projected Arctic warming.…”
Section: Discussionmentioning
confidence: 99%
“…An assessment of all terms of the Arctic heat budget and the feedback mechanisms leading to Arctic Amplification is, however, beyond the scope of our paper. The magnitude of TO-HTR changes appears to play a decisive role in the amplitude of pan-Arctic warming, and sea-ice evolution in climatechange simulations (Mahlstein and Knutti, 2011). These authors concluded that the TOHTR changes contribute significantly to Arctic amplification, but they also identified considerable differences in the TOHTR magnitude in the CMIP3 model suite as a cause for model uncertainty in projected Arctic warming.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the warming delay in the North Atlantic is often attributed to a weakening of the Atlantic Meridional Overturning Circulation (AMOC) in a warming climate, resulting in a cooling tendency (Russell and Rind 1999;Wood et al 1999;Weaver et al 2007;Xie and Vallis 2011;Kim and An 2013;Drijfhout et al 2012;Rugenstein et al 2013;Winton et al 2013). The mechanisms behind Arctic amplification are vigorously debated in the literature and involve a complex interplay of local climate feedbacks and atmospheric and oceanic heat transport (e.g., Holland and Bitz 2003;Serreze and Barry 2011;Hwang et al 2011;Mahlstein and Knutti 2011;Kay et al 2012). Our study helps to clarify some of these questions.…”
Section: Introductionmentioning
confidence: 93%
“…Presence or absence of sea ice cover impacts the intensity and frequency of winter extreme precipitation and temperature events (temperature minima, number of heavy precipitation days and number of ice days). For some of the analyzed extreme weather indices, the difference between the responses with and without 1 3 cloud and water vapor radiative forcing (Vavrus and Harrison 2003;Graversen and Wang 2009;Kapsch et al 2013) and changes in ocean heat transport (Polyakov 2005;Mahlstein and Knutti 2011;Stroeve et al 2011).…”
Section: Introductionmentioning
confidence: 99%